Adsorption mercury, cobalt, and nickel with a reclaimable and magnetic composite of hydroxyapatite/Fe3O4/polydopamine. Issue 4 (August 2021) - Foroutan, Rauf; Peighambardoust, Seyed Jamaleddin; Ahmadi, Amir; Akbari, Ali; Farjadfard, Sima; Ramavandi, Bahman
Abstract: In the current investigation, the adsorptive performance of hydroxyapatite (HAp) was improved by using Fe3 O4 magnetic nanoparticles and polydopamine (PDA) and was applied to eliminate Hg(II), Co(II), and Ni(II). The tests of XPS, XRD, EDX, FTIR, TGA, and VSM were applied to identify the HAp/Fe3 O4 /PDA structure and adsorption mechanisms. Based on the finding, pH was of the most effective variables in the elimination process and the highest yield was determined at pH 6 for all studied metals. The equilibrium data followed the Langmuir and Freundlich models (R 2 > 0.9). According to isotherm modeling, Hg(II), Co(II), and Ni(II) removal using HAp/Fe3 O4 /PDA has a physical mechanism. The highest elimination capacity (qm ) for Hg(II), Co(II), and Ni(II) was set at 51.73 mg/g, 49.32 mg/g, and 48.09 mg/g, respectively. The effect of contact time had a good consistency with the findings of the Weber and Morris kinetic, as the process was done in two steps. The Gibbs free energy parameter revealed that the abatement process is spontaneous and its spontaneity degree decreases with elevating temperature. Various analyzes were used to explore the characteristics of the HAp/Fe3 O4 /PDA composite. In summary, HAp/Fe3 O4 /PDA had an effective capability to remove toxic metals from distilled water and landfill leachate. Graphical Abstract: ga1 Highlights: Hydroxyapatite (HAp) was magnetically composited with Fe3 O4 and polydopamine (PDA). The crystalline and mesoporous adsorbent of HAp/Fe3 O4 /PDA had a BET area > 37 m 2 /g. The highest metal removal efficiency (> 92%) was obtained at pH 6. The highest elimination capacity for Hg, Co, and Ni was obtained > 48 mg/g. HAp/Fe3 O4 /PDA was used to remove metals from a landfill leachate.